PENGARUH LOKASI, PERSEPSI HARGA, DAN KUALITAS PELAYANAN TERHADAP KEPUASAN PELANGGAN DI FORE COFFEE SHOP SURABAYA - Yusril Andrianto; Zawawi (POLITEKNIK LP3I JAKARTA, 2024)
This research aims to determine the influence of location, price perception and service quality on customer satisfaction at Fore Coffee Shop Surabaya. The population in this study was the people of Surabaya City, male and female, from young people to adults. With a research sample of 96 respondents, namely people who have made repeat purchases at Fore Coffee Shop Surabaya more than once. The method used in this research is a quantitative method with the SEM PLS analysis technique. The research results show that location, price perception, and service quality have a positive effect on customer satisfaction.